Cytological Screening of the Cervical Cancer and its Significance after Menopause - Malarewicz, Andrzej (Menopause Review/Przegląd Menopauzalny, 2003)
Cytologic diagnostics is still the most important auxiliary investigation in clinical evaluation of normal, and pathological cervix. Sensivity of cytologic evaluation was significantly improved after Bethesda protocol introduction. During cytologic screening of cervical carcinoma the following questions are still actual: how often and at what age women should be examined, and what kind of follow-up should be chosen for women with normal and abnormal results of cytologic diagnostics. Author introduces various points of view concerning to this topic, regarding especially group of women after menopause. Author underlines great usefulness of colposcopy and tests for DNA HPV hybridization in diagnostics of cervival lesions. In author’s opinion clinical evaluation including both cytologic diagnostics and colposcopy is optimal in diagnostics of cervical lesions.